Dynamics for the Stochastic Plate Equations of Kirchhoff Type on $\mathbb{R}^n$ (Journal of Partial Differential Equations, 2025)
In this paper, we study mainly the long-time behavior of the stochastic plateequations of kirchhoff type with nonlinear damping on unbounded domains. Dueto the lack of compactness of Sobolev embeddings on unbounded domains, pullbackasymptotic compactness of cocycle associated with the system is proved by the tail-estimates method and splitting technique.